Lineage‐dependent effects of aryl hydrocarbon receptor agonists contribute to liver tumorigenesis. Issue 2 (5th January 2015) - Harrill, Joshua A.; Parks, Bethany B; Wauthier, Eliane; Rowlands, J. Craig; Reid, Lola M.; Thomas, Russell S.
<x xml:space="preserve">Abstract</x> Rodent cancer bioassays indicate that the aryl hydrocarbon receptor (AHR) agonist, 2, 3, 7, 8‐tetracholorodibenzo‐p‐dioxin (TCDD), causes increases in both hepatocytic and cholangiocytic tumors. Effects of AHR activation have been evaluated on rodent hepatic stem cells (rHpSCs) versus their descendants, hepatoblasts (rHBs), two lineage stages of multipotent, hepatic precursors with overlapping but also distinct phenotypic traits. This was made possible by defining the first successful culture conditions for ex vivo maintenance of rHpScs consisting of a substratum of hyaluronans and Kubota's medium (KM), a serum‐free medium designed for endodermal stem/progenitor cells. Supplementation of KM with leukemia inhibitory factor elicited lineage restriction to rHBs. Cultures were treated with various AHR agonists including TCDD, 6‐formylindolo‐[3, 2‐b]carbazole (FICZ), and 3‐3'‐diindolylmethane (DIM) and then analyzed with a combination of immunocytochemistry, gene expression, and high‐content image analysis. The AHR agonists increased proliferation of rHpSCs at concentrations producing a persistent AHR activation as indicated by induction of Cyp1a1. By contrast, treatment with TCDD resulted in a rapid loss of viability of rHBs, even though the culture conditions, in the absence of the agonists, were permissive for survival and expansion of rHBs. The effects were not observed with FICZ and at lower concentrations of DIM. Conclusion: Our findings are consistent with a lineage‐dependent mode of action for AHR agonists in rodent liver tumorigenesis through selective expansion of rHpSCs in combination with a toxicity‐induced loss of viability of rHBs. These lineage‐dependent effects correlate with increased frequency of liver tumors. (Hepatology 2015;61:548‐560)